'Gold Standard' Legislation for Adults Only: Reconceptualising Children as 'Adjoined Victims' Under the Domestic Abuse (Scotland) Act 2018. (December 2022) - Cairns, Ilona; Callander, Isla
In this article we argue that the Domestic Abuse (Scotland) Act 2018 should not be regarded as 'gold standard' in the way in which it seeks to recognise the harms caused to children who experience intimate partner coercive control in their living environment. We argue that children should be reconceptualised children as 'adjoined victims' of intimate partner domestic abuse and that the 2018 Act should be amended to include a parallel section 1 offence of 'abusive behaviour towards partner or ex-partner and adjoined child'. By offering the first academic analysis of why and how the criminal law should seek to capture children's experiences of coercive control, this article contributes to broader discussions about criminalising coercive control and the scope of such offences. It highlights key lessons that can be learnt from the Scottish story so far and sounds a note of caution against simply 'rolling out' the Scottish approach elsewhere.